2018
DOI: 10.1016/j.jmb.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Biofilm-controlling Response Regulator BfmR from Acinetobacter baumannii Reveals Details of Its DNA-binding Mechanism

Abstract: The rise of drug-resistant bacterial infections coupled with decreasing antibiotic efficacy poses a significant challenge to global health care. Acinetobacter baumannii is an insidious, emerging bacterial pathogen responsible for severe nosocomial infections aided by its ability to form biofilms. The response regulator BfmR, from the BfmR/S two-component system, is the master regulator of biofilm initiation in A. baumannii and is a tractable therapeutic target. Here we present the structure of A. baumannii Bfm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 61 publications
3
68
1
Order By: Relevance
“…On average, the Cα backbone align with an average RMSD of about 0.9 Å across ∼110 atoms (Figure 3). The asymmetric unit of BfpR contains one monomer with an adjacent symmetry mate forming the biologically relevant dimer ( Figure 2B) as described previously (Milton et al, 2017;Draughn et al, 2018). The dimer α4-β5-α5 interface of BfpR contains major salt bridges between Lys92 and Glu112, Asp102 and Arg116, and Asp101 and Arg123.…”
Section: Structure Of Bfpr N-terminal Receiver Domainmentioning
confidence: 80%
See 3 more Smart Citations
“…On average, the Cα backbone align with an average RMSD of about 0.9 Å across ∼110 atoms (Figure 3). The asymmetric unit of BfpR contains one monomer with an adjacent symmetry mate forming the biologically relevant dimer ( Figure 2B) as described previously (Milton et al, 2017;Draughn et al, 2018). The dimer α4-β5-α5 interface of BfpR contains major salt bridges between Lys92 and Glu112, Asp102 and Arg116, and Asp101 and Arg123.…”
Section: Structure Of Bfpr N-terminal Receiver Domainmentioning
confidence: 80%
“…Using a 2-aminoimidazole-based compound that targets response regulators, we have previously shown that we can inhibit BfmR, a master controller of biofilm in Acinetobacter baumannii (Thompson et al, 2012;Milton et al, 2017), and F. novicida QseB (Milton et al, 2017;Draughn et al, 2018). These results suggest that response regulators are a potential therapeutic target.…”
Section: High Mg 2+ and Response Regulator-targeting Inhibitor Recovementioning
confidence: 83%
See 2 more Smart Citations
“…Although the loops and some residues may undergo conformational changes during phosphorylation, there is no dramatic structural rearrangement in the main secondarystructure architecture of receiver domains (Lee et al, 2001). For example, the difference is small between the structures of BeF 3 À BfmRN and the apo form BfmRN, with an RMSD of 0.315 across 227 C atoms (Draughn et al, 2018). The structural differences between PA1611REC in the apo form and the complex model are also small, with an RMSD of 0.43 Å .…”
Section: Structural Alterations In Receiver Domainsmentioning
confidence: 99%